2015
DOI: 10.1142/s2010135x15300030
|View full text |Cite
|
Sign up to set email alerts
|

Ferrielectricity in DyMn2O5: A golden touchstone for multiferroicity of RMn2O5 family

Abstract: The RMn 2 O 5 manganite compounds represent one class of multiferroic family with magnetic origins, which has been receiving continuous attention in the past decade. So far, our understanding of the magnetic origins for ferroelectricity in RMn 2 O 5 is associated with the nearly collinear antiferromagnetic structure of Mn ions, while the exchange striction induced ionic displacements are the consequence of the spin frustration competitions. While this scenario may be applied to almost all RMn 2 O 5 members, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 71 publications
(180 reference statements)
1
9
0
Order By: Relevance
“…P IC , against magnetic field H , is much more remarkable than that of polarization P C between T N1 and T N2 . This effect fits the scenario of P IC  ~ ( S i × S j ), noting that the noncollinear spin structure is usually more sensitive to varying H than the collinear structure3638.…”
supporting
confidence: 74%
See 3 more Smart Citations
“…P IC , against magnetic field H , is much more remarkable than that of polarization P C between T N1 and T N2 . This effect fits the scenario of P IC  ~ ( S i × S j ), noting that the noncollinear spin structure is usually more sensitive to varying H than the collinear structure3638.…”
supporting
confidence: 74%
“…It has been repeatedly confirmed that the Mn spin orders in RMn 2 O 5 systems are highly robust against external magnetic field383940. A magnetic field of several Tesla seems not to shake much the Mn spin orders.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Besides magnetoelectric properties, RMn 2 O 5 shows the ability to be a good magnetic refrigerant at cryogenic temperature. 29,[33][34][35][36] However, the members of the family RCrTiO 5 isostructural to RMn 2 O 5 were paid very little attention. [37][38][39] In orthorhombic RCrTiO 5 , the Cr 3+ ions are interspaced between the R 3+ and Ti 4+ ions and the Cr 3+ spins are collinear along the crystallographic c axis whereas the moments of R 3+ lie on the ab plane.…”
Section: Introductionmentioning
confidence: 99%